DAMPAK ANGKUTAN SEDIMEN TERHADAP PEMBENTUKAN DELTA DI MUARA SUNGAI BONE, PROVINSI GORONTALO - Ari Mulerli (Widyariset, 2010)
Big sediment transport that caused the agradation has been created at estuary. The sediment transport settling procces at estuary made the river bed elevation increasing, otherwhise, this fenomenom can closed the connector area between estuary with the coastal and ocean. Evaluation has been done to observe the effect of sediment transport due to estuary changes. In implementation, case study about the agradation at estuary of Bone River, Gorontalo. In this studi, characteristics of estuary are observed first to get the information about the morfological of study area. The evaluation uses Surface-Water Modelling System (SMS) as the main software to analysis. From the numerical model with do nothing scenario shows that the agradation will be created among 36.18 cm every year and if we improvment the estuary, agradation will reduce about 28.14 % and the average of bed level changes about 25.99 cm.